COMPLETE RUMEN MODIFIER SUPPLEMENTATION IN CORN COB SILAGE BASAL DIET OF LAMB REDUCES METHANE EMISSION - Dwi Yulistiani; Wisri Puastuti; Budi Haryanto; Agung Purnomoadi; M. Kurihara; Amlius Thalib (Indonesian Agency for Agricultural Research and Development, 2017)
Feeding animal with fibrous materials such as corn cob will emit methane. Complete rumen modifier (CRM) is an improved feed additive comprised a mixture of Sapindus rarak, sesbania, albizia leaves and minerals that functions as a methane inhibitor. The study aimed to determine the effect of CRM supplementation on the feed intake, nutrient digestibility, rumen fermentation, methane emission and growth of lambs. The experiment was designed in a complete randomized block, four levels of CRM (0%, 1%, 2%, and 3%), six group of 24 male lambs per treatment based on the body weight. Basal diet used was corn cob silage ad libitum and concentrate (500 g/day) as a supplement. The results showed that CRM supplementation did not affect feed consumption and average daily gain, but significantly decreased the dry matter, as well as organic matter and protein digestibility. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) digestibility linearly decreased with increasing level of CRM. Ruminal pH, ammonia concentration and volatile fatty acid (VFA) concentration were not affected by the CRM supplementation. Methane production expressed in kJ/MJ gross energy (GE) or digestible energy (DE) intake significantly decreased by 32% at the 2–3% CRM supplementation and reduced by 39% when methane production was expressed in g/kg digested NDF. It can be concluded that 2% CRM supplementation in the corn cob basal diet did not affect nutrient intake and growth rate of the lamb, as well as rumen fermentation. The study suggests that CRM is an environmentally friendly feed additive for lamb